Using simulation in verification of a mathematical model for predicting the performance of manual assembly line occupied with flexible workforce. (18th December 2014) - Al–Zuheri, Atiya; Luong, Lee; Xing, Ke
Designing a dynamic system with inherent randomness requires a predictable and dependable mathematical model accurately representing the essential aspects of real systems. So it is necessary to establish a confidence level in the mathematical model of this system by carrying out a verification process for this model to collect evidence. This paper deals with verification of the mathematical model designed for the prediction of performance of manual assembly lines occupied by a flexible workforce referred to as walking worker(s) assembly line (WWAL). To verify the mathematical model, it was applied to an illustrative industrial example. Also experiments carried out on this example were simulated using a software package. Then, the predicted results of the mathematical model were compared with simulation results. Comparison leads to the verification of both the accuracy and the serviceability of the mathematical model developed.